ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA (INCOME SMOOTHING) - Ina Setyaningtyas; Purbayu Budi Hadiprajitno (Diponegoro Journal of Accounting, 2014)
The aim of this study to examine the influence of firm size, debt to equity ratio, industry sectors, operating leverage, and profitability toward income smoothing practice among manufacture listed at Indonesia Stock Exchange within a period of three years with the selection method of purposive judgement sampling. Income smoothing is a management effort to reduce the variation in the number of reported earnings to match the desired target by manipulating earnings through accounting methods or through transactions.Statistical analysis used in this study was to statistically test using descriptive statistics and logistic regression models through multivariate testing. Eckel index used to classify companies that do or do not practice income smoothing.The result of this research showed that industry sectors influence the probability of income smoothing. But firm size, debt to equity ratio, operating leverage, and profitability do not influence the probability of income smoothing.